Simultaneous measurement of contractile force and field potential of dynamically beating human iPS cell-derived cardiac cell sheet-tissue with flexible electronics. Issue 20 (24th August 2021) - Ohya, Takashi; Ohtomo, Haruki; Kikuchi, Tetsutaro; Sasaki, Daisuke; Kawamura, Yohei; Matsuura, Katsuhisa; Shimizu, Tatsuya; Fukuda, Kenjiro; Someya, Takao; Umezu, Shinjiro
Abstract : We show a novel simultaneous measurement system for contractile force and field potential of hiPSC cardiac cell sheet-tissues using flexible electronics. This system will contribute to gaining new insight in pharmacological study of human heart. Abstract : Human induced pluripotent stem (iPS) cell-derived cardiomyocytes are used for in vitro pharmacological and pathological studies worldwide. In particular, the functional assessment of cardiac tissues created from iPS cell-derived cardiomyocytes is expected to provide precise prediction of drug effects and thus streamline the process of drug development. However, the current format of electrophysiological and contractile assessment of cardiomyocytes on a rigid substrate is not appropriate for cardiac tissues that beat dynamically. Here, we show a novel simultaneous measurement system for contractile force and extracellular field potential of iPS cell-derived cardiac cell sheet-tissues using 500 nm-thick flexible electronic sheets. It was confirmed that the developed system is applicable for pharmacological studies and assessments of excitation–contraction coupling-related parameters, such as the electro-mechanical window. Our results indicate that flexible electronics with cardiac tissue engineering provide an advanced platform for drug development. This system will contribute to gaining new insight in pharmacological study of human cardiac function.